Penggunaan Sifat Pengingat Asosiatif Pada Jaringan Syaraf Tiruan Hopfield Diskret Untuk Pemulihan Data - Agung Mubyarto (Dinamika Rekayasa, 2009)
This research concern with application of discrete Hopfield neural networks for recovering data. Using associative memories properties of discrete Hopfield neural networks we can store a set of data patterns as a memories. The basic concepts of using discrete Hopfield neural networks as associative memories is to interpret the system’s neurons evolution as a movement of input pattern toward the one stored pattern most resembling the input pattern. The result shows that the application could recover false data to its origin.